Factors of stability and sustainable development in Jordan in its first centenary 1921–2021 (an analytical descriptive study) - Mohammad Saleh Bani Issa (Heliyon, 2023)
The study aims to discover the variables that have contributed to the stability of Jordan's political system, despite the barriers and conditions that the Jordanian state has faced for more than a century in the world's tensest region. It began with a hypothesis: there is a link between Jordan's stability and the legitimacy of the regime, which is founded on voluntary consent between the leadership and the people, as well as loyalty to the leadership, belonging to the homeland, the rule of law, and respect for the constitution. The study represented Jordan's stability features, stages of development, and current position on the world's political map in the first century. The study's scientific and practical significance lies in clarifying Jordan's nature and the growth, progress, and prosperity that this country is experiencing at all levels, despite the challenges it faced during the centennial; and in assisting researchers, scholars, politicians, and decision-makers in similar countries to Jordan in determining how to benefit from Jordan's experience as a role model. The study used historical, descriptive-analytical, systems analytical, and decision-making methodologies to answer the study's questions and examine its premise. It concluded that the ruling regime's religious, historical, and political legitimacy, as well as its relationship with the Hashemites, the nature of Jordanian society, as well as the rule of law and institutions, national unity, and the strong mutual relationship between the leadership and the people, all contributed to Jordan's century-long process of political stability and development.